Developing the capability of digital financial literacy in developing countries: A Case of online loan for small entrepreneurs - Wasan Uthaileang; Supaporn Kiattisin (Heliyon, 2023)
The rapid growth of digital financial services especially during the COVID-19 outbreak, is a factor accelerating the use of online loan applications that inevitably require the knowledge of digital finance. This study used the behavior change theory and digital financial literacy to identify relevant and correlated variables to confirm positive motivational factors on digital financial skills and capability. Structure equation modeling (SEM) and path analysis were applied to find the correlation and confirm the proposed hypotheses presented. There were 400 samples of small entrepreneurs from different provinces, and online questionnaires were used for data collection. The findings showed that the knowledge and motivation variables were related and had a positive effect. It contributes to continuously building up the skills and capabilities of small entrepreneurs who need to develop their capabilities in digital financial literacy adequately in line with the changes in business and technology after the outbreak of COVID-19. This concept can apply to online loan policy for small entrepreneurs trained with motivating courses who accepted digital finance literacy's usefulness.